Bacteriophage cocktail LEC2-LEC10 for broad-spectrum control of pathogenic and uncharacterized Escherichia coli in fresh produce - Kim, Eo-Jin; Ryu, Sangryeol; Lim, Jeong-A (Frontiers in Microbiology, 2025)
BackgroundEscherichia coli is a major foodborne pathogen that causes intestinal diseases leading to severe illness. In particular, E. coli contamination in fresh produce presents a significant risk, because there are no additional sterilization processes before consumption. In this study, we characterized two novel bacteriophages, vB_EcoS_LEC2 and vB_EcoS_LEC10, and explored their use as a phage cocktail to control naturally occurring E. coli contamination in fresh foods.MethodsTwo phages were isolated, and their antimicrobial activity and target bacterial spectrum were analyzed. The efficacy of a two-phage cocktail was evaluated against E. coli O157:H7 strain mixtures and naturally occurring, unidentified E. coli present on commercially available vegetables. The bacterial receptors recognized by the phages were identified using receptor-deficient mutants. The genome sequences of the two phages were compared, focusing on receptor-binding protein genes.ResultsCharacterizations revealed that both phages belonged to the Straboviridae family and were stable under various temperatures and pH conditions. The phages were confirmed to be strictly lytic, exhibiting short latent periods of 15 and 10 min and burst sizes of 22 and 189 phage particles per infected cell for LEC2 and LEC10, respectively. LEC2 and LEC10 exhibited distinct antimicrobial spectra, each with a broad but complementary host range among E. coli strains. Combining the two phages into a cocktail leveraged their complementary host specificities, broadening the overall host range and enhancing bacterial lysis against pathogenic E. coli mixtures compared to individual phages. The cocktail remarkably reduced the viability of naturally contaminated, unidentified E. coli in fresh vegetables, demonstrating its effectiveness in targeting diverse bacterial populations. LEC2 and LEC10 recognize different receptors, specifically lipopolysaccharide (LPS) (via WaaC) and OmpC, respectively, supporting their compatibility in a cocktail optimization. Furthermore, genome analysis confirmed the absence of lysogeny-related genes, toxins, and antibiotic resistance genes, reinforcing their suitability as safe biocontrol agents for food applications.ConclusionThese results demonstrate that LEC2 and LEC10, especially when used as a cocktail, are promising antibacterial agents for controlling E. coli contamination in fresh foods. Their complementary host ranges and strong lytic activity support their application in food safety strategies aimed at reducing E. coli contamination.